KOLONI BAKTERI PADA ANAK YANG DI RAWAT DI PICU SETELAH ORAL HYGIENE DENGAN NACL - Mariyam -; Dera Alfiyanti (Universitas Muhammadiyah Semarang, 2014)
Oral health needs to be maintained, whether healthy or sick. In critically ill patients admitted to the hospital within 48 hours will change the oropharyngeal flora of the more dominant grampositive turned into agram-negative.Patients were treated in the intensive care unit by a nurse performed oral treatment using NaCl standards compliant hospital operations. This study aims to identify the number of colonies of bacteria in the mouth in children admitted to the Pediatric Intensive Care Unit (PICU) in Tugurejo hospital Semarang performed oral hygiene by using NaCl. This study design was a descriptive analytic study. The sample was a child who was treated in the PICU were performed using NaCl oral hygiene and saliva taken after 8-10 hours for the examination of bacterial colony count. Sample was determined by consecutive sampling technique. The results of statistical tests the average number of bacterial colonies 36 with a standard deviation of 92.87. Suggestions for subsequent research are expected to examine the associated number of bacterial colonies on the child performed oral hygiene with other solutions.